Arc Again And Tangent Again!

Geometry Level 3

arctan 1 3 + arctan 1 4 + arctan 1 5 + arctan 1 n = π 4 \arctan \dfrac{1}{3} + \arctan \dfrac{1}{4}+\arctan \dfrac{1}{5}+\arctan \dfrac{1}{n} = \dfrac{\pi}{4}

Find the positive integer n n such that the above equality is true.


The answer is 47.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Eli Ross Staff
Apr 11, 2016

Relevant wiki: Complex Plane

Note that tan 1 1 n \tan^{-1}\frac{1}{n} is the argument of n + i , n+i, and adding angles is essentially like multiplying the arguments. Note that ( 3 + i ) ( 4 + i ) ( 5 + i ) ( n + i ) = ( 48 n 46 ) + ( 48 + 46 n ) i . (3+i)(4+i)(5+i)(n+i) = (48n-46) + (48+46n)i.

Since the RHS is π 4 , \frac{\pi}{4}, the real and imaginary parts of the result above must be equal. Setting 48 n 46 = 48 + 46 n 48n-46 = 48+46n gives 2 n = 94 , 2n = 94, so n = 47. n=47.

Moderator note:

More generally, we can just combine all of the known terms onto one side as follows:

( n + i ) = R ( 1 + i ) ( 3 + i ) ( 4 + i ) ( 5 + i ) = R 47 + i 2220 (n+i) = R \frac{ ( 1 + i ) } { (3 + i ) ( 4 + i ) ( 5 + i ) } = R \frac{ 47 + i } { 2220 }

which shows directly that n = 47 n = 47 . You can apply this to any tan 1 \tan^{-1} angles that you want to sum / subtract.

Rishabh Jain
Mar 15, 2016

See this for a quick review of Inverse-Trigonometric-Functions.

arctan 1 3 + arctan 1 4 + arctan 1 5 = π 4 arctan 1 n \color{#20A900}{\arctan \dfrac{1}{3} + \arctan \dfrac{1}{4}+\arctan \dfrac{1}{5}}= \dfrac{\pi}{4}-\arctan \dfrac{1}{n} Taking tan \tan on both sides and using:- tan ( A + B + C ) = tan A + tan B + tan C tan A tan B tan C 1 tan A tan B tan B tan C tan C tan A arctan ( tan A ) = A and tan ( A + B ) = tan A + tan B 1 tan A tan B \color{#D61F06}{\tan(A+B+C)=\dfrac{\tan A+\tan B+\tan C-\tan A\tan B\tan C}{1-\tan A\tan B-\tan B\tan C -\tan C\tan A}}\\\\ \color{#EC7300}{\arctan(\tan A)=A} \text{ and } \color{#3D99F6}{ \tan (A+B)=\dfrac{\tan A+\tan B}{1-\tan A\tan B}}

(For the above identities see Tangent of Sums here )

1 3 + 1 4 + 1 5 1 3 4 5 1 1 3 4 1 4 5 1 5 3 = 1 1 n 1 + 1 n \dfrac{\dfrac 13 +\dfrac 14 +\dfrac 15-\dfrac{1}{3\cdot 4\cdot 5}}{1-\dfrac{1}{3\cdot4}-\dfrac{1}{4\cdot 5}-\dfrac{1}{5\cdot3}}=\dfrac{1-\dfrac{1}{n}}{1+\dfrac{1}{n}} 46 48 = n 1 n + 1 \dfrac{46}{48}=\dfrac{n-1}{n+1} 47 1 47 + 1 = n 1 n + 1 \dfrac{47-1}{47+1}=\dfrac{n-1}{n+1} n = 47 \Huge \therefore \color{#456461}{\boxed{\color{#EC7300}{\boxed{\color{#0C6AC7}{n=47}}}}}

Anish Harsha
Mar 15, 2016

Since we are dealing with acute angles, tan ( arctan a ) = a \tan(\arctan a) = a

Note that, tan ( arctan a + arctan b ) = a + b 1 a b \tan(\arctan a + \arctan b)= \dfrac{a+b}{1-ab} , by tangent addition. Thus, arctan a + arctan b = arctan a + b 1 a b \arctan a + \arctan b = \arctan \dfrac{a+b}{1-ab}

Applying this to first two terms, we get arctan 1 3 + arctan 1 4 = arctan 7 11 \arctan \dfrac{1}{3}+ \arctan \dfrac{1}{4} = \arctan \dfrac{7}{11} .

Now, arctan 7 11 + arctan 1 5 = arctan 23 24 \arctan \dfrac{7}{11} + \arctan \dfrac{1}{5} = \arctan \dfrac{23}{24} .

We now have arctan 23 24 + arctan 1 n = π 4 = arctan 1 \arctan \dfrac{23}{24}+ \arctan \dfrac{1}{n} = \dfrac{\pi}{4} = \arctan 1 .

Thus, 23 24 + 1 n 1 23 24 n \dfrac{\dfrac{23}{24} + \dfrac{1}{n}}{1- \dfrac{23}{24n}} and simplifying ;

23 n + 24 = 24 n 23 n = 47 23n +24= 24n - 23 \to n = 47

Sridhar Sri
Mar 15, 2016

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...